2009
DOI: 10.1016/j.pain.2009.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal membrane permeability and hypersensitivity in the irritable bowel syndrome

Abstract: Irritable bowel syndrome (IBS) is a common gastrointestinal disorder in which the underlying pathophysiology is poorly understood; however, increased intestinal permeability in diarrhea-predominant IBS patients has been reported. Here we demonstrate diarrhea-predominant IBS patients (D-IBS) that display increased intestinal permeability. We have also found that increased intestinal membrane permeability is associated with visceral and thermal hypersensitivity in this subset of D-IBS patients. We evaluated 54 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
285
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(315 citation statements)
references
References 47 publications
16
285
1
5
Order By: Relevance
“…Unlike previous studies, no strong correlations between the severity of symptoms and experimental parameters were found in our study (Zhou et al, 2009), indicating that the mechanisms involved in the expression of symptoms are still complicated and inadequately understood. A strength of our study was that our analysis excluded the confounding effects of mental factors.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike previous studies, no strong correlations between the severity of symptoms and experimental parameters were found in our study (Zhou et al, 2009), indicating that the mechanisms involved in the expression of symptoms are still complicated and inadequately understood. A strength of our study was that our analysis excluded the confounding effects of mental factors.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we confirmed that D-IBS patients have somatic hypersensitivity using both cold and ischemic sensitivity tests. Our results were similar to those of previous studies (Zhou et al, 2009;. To our knowledge, our work is the first study to use diverse methods, especially the ischemic sensitivity test, to examine somatic sensitivity in China.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…128,129 In a series of pivotal studies, Zhou and coworkers determined the importance of miR-29 on visceral hypersensitivity via a mechanism involving increased intestinal permeability. 34,130,131 Increased expression of mi-R-29a and miR29b were associated with increased intestinal permeability in mice following stress exposure. In support of a role miR-29 they employed Mir29 -/-mice and discovered that stress-induced intestinal permeability was significantly attenuated via a mechanism involving regulation of Claudin-1 mRNA expression.…”
Section: Epigenetic Mechanisms That Contribute To Irritable Bowel Synmentioning
confidence: 99%
“…Single-nucleotide polymorphisms in CDH1 , which encodes the tight junction protein E-cadherin, are associated with increased risk of post-infectious IBS ( 40 ). Detailed molecular studies of the epithelial barrier indicate the expression and subcellular distribution of tight junction proteins are substantially altered in IBS patients ( 41 -44 ), and impaired intestinal permeability has been shown to correlate with pain / discomfort and / or bowel habit ( Table 1 ) ( 34,37,41,43 ). However, impaired barrier defenses are unlikely to directly cause pain, but instead ease access of luminal contents to the GI wall, promoting infl ammatory responses and modulating sensory-motor function.…”
Section: Are Barrier Defenses Altered In Ibs?mentioning
confidence: 99%